Charge sharing non-binary SAR ADC - Chen, Xiangchen (2013)
This paper presents a non-binary passive charge sharing SAR ADC and an optimization method for non-binary successive approximation algorithm. The passive charge sharing ADC is designed. The optimization method suggests that the non-binary SAR ADC with lower standard deviation DAC capacitance values will show better static performance. The SAR ADCs with different standard deviation value of DAC capacitor array are designed and simulated using a commercial 65nm CMOS technology. The simulation result shows that the static performance improvement trend is in accordance with the proposed optimization method. In addition, the optimized non-binary charge sharing SAR ADC shows better performance than conventional binary SAR ADC.